2015
DOI: 10.5137/1019-5149.jtn.16572-15.1
|View full text |Cite
|
Sign up to set email alerts
|

Patient selection and efficacy of intradiscal electrothermal therapy with respect to dallas discogram score

Abstract: ABSTRACTatic annular tears can be treated percutaneously with the minimally invasive IDET procedure.Disc morphology was first defined by Adams et al., who showed the morphological view of the disc using a discogram (1). The extent and dimensions of the annular tear are thought to be more important than the disc degeneration itself as the basis for discogenic pain based on computed tomography (CT) discography studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
1
Order By: Relevance
“…A previous study on IDET showed that clinical improvements could be realized after IDET in select surgical candidates with mild disc degeneration and HIZ on MRI, discography, and lowgrade Dallas Discogram Scale, with more effective treatment results. [47] On the other hand, the presence of disc herniation on MRI showed a more successful outcome in our study and showed no significant relationship with HIZ on MRI. This might be due to the disc decompression effect of the intradiscal treatment.…”
Section: Clinical Factorscontrasting
confidence: 48%
“…A previous study on IDET showed that clinical improvements could be realized after IDET in select surgical candidates with mild disc degeneration and HIZ on MRI, discography, and lowgrade Dallas Discogram Scale, with more effective treatment results. [47] On the other hand, the presence of disc herniation on MRI showed a more successful outcome in our study and showed no significant relationship with HIZ on MRI. This might be due to the disc decompression effect of the intradiscal treatment.…”
Section: Clinical Factorscontrasting
confidence: 48%
“…Once the catheter's tip is in the posterior region of the fibrous annulus, it is heated up to 90°C (194°F), destroying the nociceptor terminations [8]. It last approximately 15 minutes and is an outpatient procedure [18].…”
Section: Intradiscal Electrothermal Therapy (Idet)mentioning
confidence: 99%